2017
DOI: 10.7150/jca.17872
|View full text |Cite
|
Sign up to set email alerts
|

A Combined ULBP2 and SEMA5A Expression Signature as a Prognostic and Predictive Biomarker for Colon Cancer

Abstract: Background: Prognostic biomarkers for cancer have the power to change the course of disease if they add value beyond known prognostic factors, if they can help shape treatment protocols, and if they are reliable. The aim of this study was to identify such biomarkers for colon cancer and to understand the molecular mechanisms leading to prognostic stratifications based on these biomarkers.Methods and Findings: We used an in house R based script (SSAT) for the in silico discovery of stage-independent prognostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 37 publications
0
26
1
Order By: Relevance
“…In line with our earlier findings 27 , we show here for the first time in vitro, that Lapatinib and Midostaurin are candidates for such combination therapy, as they target selectively either NS/E or CS/M cells, respectively. Even though EMT might be a signature shared among tumor types, combination treatment suggestions obtained for breast cancer in this study are different from those we found for other tumor types, such as colon cancer and melanoma 68,69 . One explanation for this can be that NS/E and CS/M cell types defined for tumors originating from different tissues actually define different phenotypes in the EMT or plasticity scale.…”
Section: Discussioncontrasting
confidence: 99%
“…In line with our earlier findings 27 , we show here for the first time in vitro, that Lapatinib and Midostaurin are candidates for such combination therapy, as they target selectively either NS/E or CS/M cells, respectively. Even though EMT might be a signature shared among tumor types, combination treatment suggestions obtained for breast cancer in this study are different from those we found for other tumor types, such as colon cancer and melanoma 68,69 . One explanation for this can be that NS/E and CS/M cell types defined for tumors originating from different tissues actually define different phenotypes in the EMT or plasticity scale.…”
Section: Discussioncontrasting
confidence: 99%
“…p < 0.05 was considered as statistically significant. Log-rank tests using all cut-off values (LRMC) for a given dataset were obtained using an in-house, R-based script [23]. Specific statistical analyses are further explained in the figure legends.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Jin et al [24] found that SEMA5A played a role in cardiac morphogenesis and regeneration. Several studies have also implicated SEMA5A in tumor progression [25-29].…”
Section: Introductionmentioning
confidence: 99%